Phyto-mediated green synthesis of CeO2–ZnO nanoparticles using glycosmis mauritiana leaf extract: Antibacterial activity and photodegradative applications. (2022) - Rosi, H.; Janci, M.; Preethi, M.
Abstract: A simple novel green synthesis of the nano compound cerium oxide doped with zinc oxides (CeO2 –ZnO) was produced with a reduction agent of glycosmis mauritiana leaf extracted. The compounds synthesized are characterized by × - ray diffraction, UV, DRS and TEM. The results show that the prepared materials were superior in performance as compared to unoped ZnO and CeO2 particles, due to alternation in band gap, surface adsorption and enhanced photoresponsive. The photocatalytic efficiency of the CeO2 -ZnO series was evaluated against Acid black 1 and the antibacterial properties were checked against the clinical bacteria strains. All findings showed that CeO2 -ZnOs' photocatalytical and antibacterial activities with various CeO2 material are superior to the pure ZnO activities.